Multimodality treatment of rectal cancer – Cancer Centre, Gliwice branch experience - Chmielarz, Andrzej; Chmielnik, Ewa; Plewicki, Grzegorz; Słomian, Grzegorz; Wideł, Maciej; Lasek-Kryj, Magdalena; Zeman, Marcin; Kryj, Mariusz; Suwiński, Rafał (Contemporary Oncology/Współczesna Onkologia, 2003)
A group of 132 cases (55 females and 77 males) of T 1-4 N 0-+ M 0-1 rectal cancer was subject to analysis. The average age was 62. The group of 75 patients was preoperatively irradiated using 4 different treatment schemes (25 Gy/5 Gy/fr, 42.5 Gy/1.8 Gy/fr, 30 gy/3 Gy/fr, 42 Gy/2 x 1.5 Gy/fr). All patients were treated surgically, abdomino-perineal resection (APR) was performed in 51 (43%) cases and low anterior resection (LAR) in 61 (52%), Hartman procedure was done in 3 (2%) and local excision in 2 (1.5%) cases. 15 (11%) patients were intraoperatively assessed as unresectable. Mean follow-up time was 12 months. 24-month disease-free survival (DFS) was 56.2% for the entire group, and was found to be significantly longer among patients who received preoperative radiotherapy: 63.9 vs. 36.2% (p=0.008). Local recurrence-free survival time was almost twice longer among irradiated patients (89% vs. 54%). No significant correlation was found between survival time and the preoperative treatment scheme. Of the entire group of patients, 31 (23%) of them developed distant metastases (DM) and 17 (13%) local recurrence (LR). LR rate was significantly higher in the non-irradiated group. A remarkably downstaging effect was noticed in the irradiated group. Preoperative radiotherapy did not affect the possibility of performing sphincter saving procedures. Preoperative radiotherapy is significantly influencing survival time and the risk of local failure. Effectiveness of different schemes of radiotherapy has to be assessed in prospective studies.